Francine Krause: Reconnecting Women to the Motherlines through the Practice of Pregnancy Belly Masking - Williams, Bianca (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
In the early 1990s, academic feminists concerned with essentialism were skeptical of an excessive focus on motherhood and the pregnant body, yet in popular culture, the pregnant body was being galvanized as a symbol of female empowerment. At that time, Naomi Lowinsky also introduced her concept of the “motherlines,” calling for women to regain a sense an embodied connection to the stories of their lifecycles and maternal lineage. Interpreting the motherlines in a nonessentialist way, I introduce Californian artist Francine Krause’s 1991 “In Honor of Pregnant Women” exhibition of belly masks (i.e., plaster casts of the pregnant torso) as an example of a cultural practice working toward reconnecting women to the motherlines through the language of visual art. Krause’s exhibition provided a forum through which everyday women’s stories and feelings about pregnancy could be publicly transmitted; it called attention to women’s entry into, and complex relationship with, the “mask of motherhood.” Krause’s exhibition was also an important way for women to mediate their complex feelings about pregnancy, which allowed the audience to question established cultural discourses about pregnancy as well as consider their own connection to the motherlines.